2004
DOI: 10.1210/jc.2004-0558
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Expression of the Gsα Gene in Human Bone and Adipose Tissue

Abstract: Mutations of the Gsalpha gene inherited from the mother lead to pseudohypoparathyroidism (PHP) type Ia (PHP Ia), in which Albright's hereditary osteodistrophy is associated to resistance to the action of different hormones, whereas the same mutations inherited from the father lead to isolated Albright's hereditary osteodistrophy [pseudo-PHP (PPHP)]. Accordingly, it has been suggested that Gsalpha is under tissue-specific imprinting control, and recent studies provided evidence for a predominant maternal origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 29 publications
7
82
0
Order By: Relevance
“…Our ΔNesp55 m /Gnasxl m+/p− mice demonstrated a normal calcemic response to PTH administration, indicating that the actions of PTH on bone are not impaired, as is also true in patients with PHP-Ib (48). This result likely reflects the absence of paternal Gαs silencing in this tissue (13).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our ΔNesp55 m /Gnasxl m+/p− mice demonstrated a normal calcemic response to PTH administration, indicating that the actions of PTH on bone are not impaired, as is also true in patients with PHP-Ib (48). This result likely reflects the absence of paternal Gαs silencing in this tissue (13).…”
Section: Discussionmentioning
confidence: 77%
“…The most downstream alternative first exon is Gαs exon 1, which generates transcripts encoding the ubiquitously expressed Gαs (6). The Gαs promoter resides within a nonmethylated CpG island, but despite the absence of differential methylation at its promoter, Gαs shows predominantly maternal expression in some tissues, including pituitary, thyroid, renal proximal tubules, and gonads (7-10); Gαs expression is biallelic in most other tissues (11)(12)(13). The furthest upstream alternative promoter generates transcripts that encode the neuroendocrine-specific protein of 55 kDa (NESP55; mouse Nesp55), a chromogranin-like protein, the coding sequence of which is located within a specific upstream exon; Gαs exons 2-13 reside within the 3′ untranslated region of NESP55 transcripts (14).…”
mentioning
confidence: 99%
“…In contrast, a mutation of the paternal allele results in isolated AHO. In sum, the AHO phenotype seems to arise from plain Gs(α) haploinsufficiency [45], while multihormone resistance in patients with maternal mutations is explained by the tissue-specific imprinting of the gene (and the silencing of the paternal allele in hormone target tissues) [43].…”
Section: Haploinsufficiency and Monoallelic Expressionmentioning
confidence: 99%
“…These findings have been refuted by studies in adult G s α-specific knockout models in which G s α levels were reduced to a similar extent in WAT from maternal and paternal heterozygotes (Germain-Lee et al, 2005) and with only a small difference in G s α BAT expression between maternal and paternal heterozygotes (M. Chen et al, 2005a). One study also showed no evidence for G s α imprinting in human WAT (Mantovani et al, 2004). We suspect that the differential G s α expression observed in E2 m−/+ and E2 +/p− mice may result from secondary changes in G s α expression resulting from different levels of metabolic activity in adipose tissues of these mice (S. Yu et al, 2000) rather than imprinting.…”
Section: Use Of Gnas Gene Targeting In Miceto Study Gnas Imprintingmentioning
confidence: 99%